A mathematical model of hiPSC cardiomyocytes electromechanics. Issue 22 (25th November 2021) - Forouzandehmehr, Mohamadamin; Koivumäki, Jussi T.; Hyttinen, Jari; Paci, Michelangelo
Abstract: Human induced pluripotent stem cell‐derived cardiomyocytes (hiPSC‐CMs) are becoming instrumental in cardiac research, human‐based cell level cardiotoxicity tests, and developing patient‐specific care. As one of the principal functional readouts is contractility, we propose a novel electromechanical hiPSC‐CM computational model named the hiPSC‐CM‐CE. This model comprises a reparametrized version of contractile element (CE) by Rice et al., 2008, with a new passive force formulation, integrated into a hiPSC‐CM electrophysiology formalism by Paci et al. in 2020. Our simulated results were validated against in vitro data reported for hiPSC‐CMs at matching conditions from different labs. Specifically, key action potential (AP) and calcium transient (CaT) biomarkers simulated by the hiPSC‐CM‐CE model were within the experimental ranges. On the mechanical side, simulated cell shortening, contraction–relaxation kinetic indices (RT50 and RT25 ), and the amplitude of tension fell within the experimental intervals. Markedly, as an inter‐scale analysis, correct classification of the inotropic effects due to non‐cardiomyocytes in hiPSC‐CM tissues was predicted on account of the passive force expression introduced to the CE. Finally, the physiological inotropic effects caused by Verapamil and Bay‐K 8644 and the aftercontractions due to the early afterdepolarizations (EADs) were simulated and validated against experimental data. In the future, the presented model can be readily expanded to take in pharmacological trials and genetic mutations, such as those involved in hypertrophic cardiomyopathy, and study arrhythmia trigger mechanisms. Abstract : We present the first hiPSC‐CM computational model that accounts for essential AP, CaT, and mechanical biomarkers incorporating experimental variability. The introduced passive force handling enables the model to capture the inotropic effect of non‐cardiomyocytes in hiPSC‐CM tissues. Simulated cell shortening and contraction–relaxation indices fall within experimental ranges, and EAD‐based aftercontractions predicted by the model are in accord with experimental observations. Predicted Verapamil and Bay‐K 8644 inotropic effects agree with in vitro data.